Homotopy Analysis Method for the First Order Fuzzy Volterra-Fredholm Integro-differential Equations - Ahmed A. Hamoud; Kirtiwant P. Ghadle (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
A fuzzy Volterra-Fredholm integro-differential equation (FVFIDE) in a parametric case is converted to its related crisp case.  We use homotopy analysis method to find the approximate solution of this system and hence obtain an approximation for the fuzzy solution of the  FVFIDE. This paper discusses existence and uniqueness results and convergence of the proposed method.